The Policy Challenge of Private Land Management for Conservation of Yellow-Crested Cockatoo and its Habitat in Masakambing Island, Indonesia - Ihsanuddin Ihsanuddin; Kliwon Hidayat; Keppi Sukesi; Yayuk Yuliati; Sukmo Pinuji (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Yellow-crested small cockatoo (Cacatoasulphureaabbotti) is an endangered species lives in residential area with private ownership in Masakambing Island, Sumenep Regency, East Java, Indonesia. Recently, the population of the bird only remains between 22-25 birds. Their habitat requires 3 important trees to support their living: nesting trees, sleeping trees and feeding trees. However, conservation efforts are not easy as they share space for living with human. Besides that, in a small island, land is scarce and available resources are limited. Therefore, its conservation effort needs community involvement. Generally, sharing access to the land resources are intended to social and economic aspects. The study was aimed at findingout the distribution of important treesas habitat for yellow-crested cockatoo and propose land management policy in supporting its conservation activities in Masakambing. The analysis uses qualitative method with interactive model. The results showed that 90% of the bird’s habitat was in a residential area with private ownership. The Private Land Conservation policy with conservation easement approach can be implemented to conserve yellow-crested cockatoo in Masakambing. Unfortunately, the Private land Conservation Policy and conservation easement approach hasnot been regulated clearly.